2022
DOI: 10.1158/2326-6066.cir-22-0387
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of Tumors Is Regulated by T cell–Intrinsic Nitric Oxide Synthesis

Abstract: Nitric oxide (NO) is a signaling molecule produced by NO synthases (NOS1-3) to control processes such as neurotransmission, vascular permeability, and immune function. Although myeloid cell-derived NO has been shown to suppress T-cell responses, the role of NO synthesis in T cells themselves is not well understood. Here, we showed that significant amounts of NO were synthesized in human and murine CD8+ T cells following activation. Tumor growth was significantly accelerated in a T cell-specific, Nos2-null mous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Highlighting the direct antagonistic effect of NOS uncoupling on T cell activity, de Sanctis et al found that inhibiting ARG1 and NOS2 expression inhibited accumulation of nitro-Tyrosine moieties in T cells and sensitized pancreatic tumor models to attack by TERT specific CAR-T (33). In addition to modulating the negative effects of NOS uncoupling, restoring native NO production and downstream signaling by activated T cells has also been proposed as an attractive therapeutic strategy (87).…”
Section: Bh4 Metabolism In Tumorigenesis Bh4 and Immune Escapementioning
confidence: 99%
“…Highlighting the direct antagonistic effect of NOS uncoupling on T cell activity, de Sanctis et al found that inhibiting ARG1 and NOS2 expression inhibited accumulation of nitro-Tyrosine moieties in T cells and sensitized pancreatic tumor models to attack by TERT specific CAR-T (33). In addition to modulating the negative effects of NOS uncoupling, restoring native NO production and downstream signaling by activated T cells has also been proposed as an attractive therapeutic strategy (87).…”
Section: Bh4 Metabolism In Tumorigenesis Bh4 and Immune Escapementioning
confidence: 99%